A method of calculating water and soil loading on top of shallow shield tunnels near water areas - Zhu, Zeqi; Chang, Liuming; Cui, Lan; Sheng, Qian (Frontiers in Earth Science, 2023)
Long-term water seepage in shield tunnels has a serious impact on water and soil loading on the outer surfaces of a shield segment near water areas. A theoretical analysis was used to obtain a formula to express the average vertical seepage gradient at the top of the tunnel. A formula for calculating the coefficient of lateral earth pressure for the principal stress arch effect was utilized. A model that takes into consideration the effects of long-term water seepage on the shield tunnel’s water and soil load was designed. Based on this calculation model, the variation law of the water and soil loading on top of shield tunnel near water area with the internal friction angle in the soil body, the density of the soil, the tunnel depth-to-diameter ratio, the water head of the external section, and the amount of water seepage per unit length is studied. Based on the geological conditions and field survey results of water and soil loading of two typical segments of the Maliuzhou Waterway section of the Hengqin Tunnel, a comparative analysis of the theoretical results and field survey measurements was performed for different calculated conditions. The research shows that the proposed model is able to perform a reasonably effective evaluation of the water and soil pressure at the top of the shield tunnel for the marine and land segments of the shield tunnel; and, when compared with Dimitrios Kolymbas’ effective stress method and Terzaghi’s Principle, the method shown in this paper has fewer errors. The results of the associated research are sufficient to reasonably design and propose a theoretical basis for underwater shield tunnels.